2019
DOI: 10.1021/acs.orglett.9b00191
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Reductive Cyclization of o-Nitroarenes via Biradical Recombination

Abstract: A visible-light-induced/thiourea-mediated intramolecular cyclization of o-nitroarenes under mild conditions is realized for the first time, which provides an efficient and environmentally friendly way to access pharmaceutical relevant quinazolinone derivatives. The reaction can be easily extended to gram level by using a continuous-flow setup with high efficiency. Mechanistic investigation including control experiments, transient fluorescence, UV–vis spectra, and DFT calculations suggests that the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…83 In 2019, Zheng reported a visible-lightmediated thiourea-catalyzed intramolecular reductive cyclization of ortho-substituted nitroarenes to produce polycyclic quinazolinones (Scheme 24). 82 Their investigations showed that making changes to the structure of the thiourea catalyst impacted the yield of the transformation. No reaction was observed in the absence of light, and the yield was severely attenuated when the silane was omitted or when air was used in place of the N 2 atmosphere.…”
Section: Short Review Synthesis 9 Visible-light-driven Reductive Amin...mentioning
confidence: 99%
“…83 In 2019, Zheng reported a visible-lightmediated thiourea-catalyzed intramolecular reductive cyclization of ortho-substituted nitroarenes to produce polycyclic quinazolinones (Scheme 24). 82 Their investigations showed that making changes to the structure of the thiourea catalyst impacted the yield of the transformation. No reaction was observed in the absence of light, and the yield was severely attenuated when the silane was omitted or when air was used in place of the N 2 atmosphere.…”
Section: Short Review Synthesis 9 Visible-light-driven Reductive Amin...mentioning
confidence: 99%
“…There are cyclizations using Pd-catalysis with CO [ 68 ] or H 2 [ 69 ]. Recent metal-free conditions use visible light, phenylthiourea as catalyst and PhSiH 3 as reductant [ 70 ], and electrochemical cyclizations [ 52 ]. Thermal annulation using nitrobenzene substrates are possible with neat 1,2,3,4-tetrahydroisoquinoline (THIQ) ( Scheme 20 a) [ 71 ], and cyclizations occur using I 2 /HCO 2 H [ 72 ] ( Scheme 20 b).…”
Section: Syntheses Of Ring-fused Benzimidazoles and Imidazobenzimidazolesmentioning
confidence: 99%
“…[39] In 2019, Zhang and co-workers firstly reported a visible-lightinduced intramolecular reductive cyclization of o-nitrobenzamides 50 for the synthesis of useful quinazolinone derivatives 51 (Scheme 25). [40] This transformation uses thiourea as a catalyst and silane as a terminal reductant under 10 W purple LED. A wild range of onitrobenzamides participated in the reaction, affording a series of polycyclic quinazolinone derivatives in good to high yields.…”
Section: Other Processes Involve Reductive Coupling Of Nitro Compoundmentioning
confidence: 99%